Efficacy of structured and conventional techniques on aesthetic and corrective rhinoplasty - Paolo Rubez Rocha (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: Rhinoplasty, like other plastic surgery subspecialties, has greatly evolved in recent decades, as both a surgical technique and a diagnosis of the alterations that need to be performed. The objective of the current study was to evaluate the efficacy of the structured and conventional surgical techniques on nasal aesthetic and corrective approaches. METHODS: A total of 49 patients, who underwent surgical operation by the author of this work, were retrospectively studied. The patient generally underwent one of the two surgical techniques. The efficacy of each technique was evaluated by means of the critique provided by the patients and the surgeon regarding the results, and the ability to reach the pre-operative goals. RESULTS: Both techniques were efficient in attaining the final objective of the surgery. Patient and surgeon satisfaction were similar in both cases, and there were no major complications in any of the groups. CONCLUSION: The present work showed that both the structured and the conventional techniques were efficient in the treatment of nasal alterations. The most important factor for selecting the best approach in each case was the correct pre-operative diagnosis of the required alterations.